Augmenting English public speaking skill through peer evaluation: a case study in Toastmaster International Club - Lailatul Rifah; Fardini Sabilah (Institut Agama Islam Negeri (IAIN) Palangka Raya, Indonesia, 2022)
Having peers to give public speaking feedback is always feasible to measure the learners’ performance. However, learners are unwilling to share their feedback in the evaluation due to hesitance. This research investigates the kind of peer evaluation elements that the Toastmaster evaluator used to evaluate the speakers and how the they interpret the evaluation given by their peers. An in-depth interview was used to analyze about the elements of peer evaluation and the speakers’ feedback towards peer evaluation. Snowballing technique was chosen to select the research subjects. Three research subjects, as the members of Toastmaster International (TMI) in Malang and Surabaya, Indonesia claimed that the elements of evaluation used in TMI increased the ability of public speaking. The assessment aspects were divided into three factors: the script, seen, and spoken. Meanwhile, other crucial evaluation elements in public speaking include the grammatical aspect and proper words instead of filler words. This research found that the TMI speakers felt very satisfied with the implementation of peer evaluation due to its effect on increasing confidence during performing public speaking. It can be implied that peer evaluation element can effectively be used to measure oral communication skills from peer’s point of view in TMI.